Patient perspectives on adverse event investigations in health care - Rachel I. Dijkstra-Eijkemans; Linda J. Knap; Nieke A. Elbers; Roland D. Friele; Antony Pemberton (BMC, 2024)
Abstract Background Over the last decade attention has grown to give patients and next of kin (P/N) more substantial roles in adverse event investigations. Adverse event investigations occur after adverse events that resulted in death or severe injury. Few studies have focused on patient perspectives on their involvement in such investigations. The present study sets out to investigate how P/N and patient representatives (client councils and the Patient Federation Netherlands) view the involvement of P/N in adverse event investigations, particularly whether and why they want to involved, and how they want to shape their involvement. Methods The study features qualitative data on three levels: interviews with P/N (personal), focus groups with representatives of client councils (institutional), and an interview with the Patient Federation Netherlands (national). Researchers used inductive, thematic analysis and validated the results through data source triangulation. Results The initiative taken by the hospitals in this study provided P/N with the space to feel heard and a position as legitimate stakeholder. P/N appreciated the opportunity to choose whether and how they wanted to be involved in the investigation as stakeholders. P/N emphasized the need for hospitals to learn from the investigations, but for them the investigation was also part of a more encompassing relationship. P/N's views showed the inextricable link between the first conversation with the health care professional and the investigation, and the ongoing care after the investigation was finalized. Hence, an adverse event investigation is part of a broader experience when understood from a patient perspective. Conclusions An adverse event investigation should be considered as part of an existing relationship between P/N and hospital that starts before the investigation and continues during follow up care. It is crucial for hospitals to take the initiative in the investigation and in the involvement of P/N. P/N motivations for involvement can be understood as driven by agency or communion. Agentic motivations include being an active participant by choice, while communion motivations include the need to be heard.